2020
DOI: 10.3389/fbioe.2020.00274
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Multi-Layer Deep Learning Based Predictive Model to Identify DNA N4-Methylcytosine Modifications

Abstract: DNA N4-methylcytosine modification (4mC) plays an essential role in a variety of biological processes. Therefore, accurate identification the 4mC distribution in genome-scale is important for systematically understanding its biological functions. In this study, we present Deep4mcPred, a multi-layer deep learning based predictive model to identify DNA N4-methylcytosine modifications. In this predictor, we for the first time integrate residual network and recurrent neural network to build a multi-layer deep lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…The bold values in the table shows high performance achieved for the particular database. Species Dataset Model Sensitivity Specificity Accuracy MCC AUC Caenorhabditis elegans ( C. elegans ) Liu et al [24] DeepTorrent 0.930 0.910 0.920 0.840 0.976 DCNN-4mC 0.971 0.968 0.969 0.938 0.992 Zeng et al [27] 4mcDeep-CBI 0.949 0.894 0.930 0.850 0.924 DCNN-4mC 0.970 0.942 0.959 0.913 0.986 Rao et al [26] Deep4mCPred 0.915 0.872 0.893 0.787 DCNN-4mC 0.955 0.951 0.953 0.906 0.982 Drosophila melanogaster ( D. melanogaster ) Liu et al …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bold values in the table shows high performance achieved for the particular database. Species Dataset Model Sensitivity Specificity Accuracy MCC AUC Caenorhabditis elegans ( C. elegans ) Liu et al [24] DeepTorrent 0.930 0.910 0.920 0.840 0.976 DCNN-4mC 0.971 0.968 0.969 0.938 0.992 Zeng et al [27] 4mcDeep-CBI 0.949 0.894 0.930 0.850 0.924 DCNN-4mC 0.970 0.942 0.959 0.913 0.986 Rao et al [26] Deep4mCPred 0.915 0.872 0.893 0.787 DCNN-4mC 0.955 0.951 0.953 0.906 0.982 Drosophila melanogaster ( D. melanogaster ) Liu et al …”
Section: Resultsmentioning
confidence: 99%
“…Some other deep learning based tools like 4mCCNN [25] were also proposed which provide improvement in performance for identification of 4mC site in these species. Further Rao et al contributed an additional datatset for C.elegans , D.melanogaster and A.thaliana [26] . Subsequently Zeng et al collected an additional dataset for C.elegans [27] .…”
Section: Introductionmentioning
confidence: 99%
“…To demonstrate the effectiveness of the proposed method, we compared its performance with four other existing single-task state-of-the-art methods on the benchmark dataset, including 4mcPred-IFL ( Wei et al, 2019b ), 4mcPred_SVM ( Wei et al, 2019a ), and Deep4mcPred ( Zeng and Liao, 2020 ). It is worth noting that among the three competing methods, except the method Deep4mcPred using deep learning technique, other methods all use traditional machine learning to train the respective models by hand-made features extracted from original DNA sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that a stringent dataset is essential for building a robust predictive model ( Liang et al, 2017 ; Zeng and Liao, 2020 ; Su et al, 2021 ). In our previous work ( Zeng and Liao, 2020 ), we constructed large-scale datasets for three species, including Arabidopsis thaliana ( A. thaliana ), Caenorhabditis elegans ( C. elegans ), and Drosophila melanogaster ( D. melanogaster ). As for the positive samples, there are 20,000 positive samples, and each sample is a 41-bp-long sequence centered with true 4mC sites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation